Evaluation of the Level of Enterprise Risk Management Adoption and Maturity of Insurance Companies in Kenya - Njagi, Caroline; Njuguna, Dr. Amos (International Journal of Finance and Accounting, 2017)
Purpose: The purpose of this study was to evaluate the extent to which insurance companies in Kenya have adopted ERM process, and then to assess the maturity, challenges and strategies in the implementation of this process. Materials and methods: The research design adopted for the study is descriptive research. The researcher conducted a survey on the 49 insurance companies of Kenya to encapsulate the factors that are relevant in articulating the extent of adoption of ERM and the level of maturity. A sample of 196 respondents was selected from a population of 245 respondents. The study used quantitative and qualitative methods of data analysis. Statistical Package for Social Sciences (SPSS) version 20 program was used for analysis. The results were presented using tables and pie charts. Similarly, qualitative data was summarized and categorized according to common themes and presentedin continuous prose form. Results: The study concluded that organizational related challenges hindered implementation of ERM programs. Results revealed that inadequate application of the risk management framework, ambiguity in roles and responsibilities in risk management, complexities in risk measurement, lack of embodiment of ERM in organizational culture, difficulty in risk quantification, linking risk information to strategic decision making, ensuring that all decisions remain within the organization's risk tolerance, proactively identifying current and emerging risks, cost and budgetary constraints, misalignment of the risk and business operating models, risk management not seen as a priority by top management and inadequate information to make risk-based decisions hindered implementation of ERM frameworks among insurance firms in Kenya. The findings imply that organization related challenges have a significant effect on ERM implementation. Recommendations: The study recommends that there should be better organizational strategies to help improve implementation of ERM programs. It was found that building a strong risk culture, engaging consultants, building a dedicated ERM function, committed board of directors and top management, developing risk appetite statement, appointment of a Chief Risk Officer (CRO) and availing ERM budgets improved the implementation of ERM programs. Key words: enterprise risk management, adoption, maturity